MOTORCYCLIST’S WILLINGNESS TO PAY FOR SLIGHT INJURIES REDUCTION DUE TO MOTOR VEHICLE ACCIDENTS (CASE STUDY: DENPASAR, BALI) - Priyantha Wedagama, D.M (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011)
This study investigates motorcyclist’s willingness to pay (WTP) for slight injuries reduction due to motor vehicle accidents in the city of Denpasar, Bali Province, using logistic regression technique. The study found that total travel distance per day by all motorcyclists in the household, groups of motorcyclists aged between 25 and 34 years old, between 35 and 44 and between 55 and 64 years old influenced about 50%, 36%, 35% and 86% respectively on motorcyclist’s WTP for 25% slight injuries reduction and about 50%, 64%, 65% and 14% respectively on motorcyclist’s WTP for 15% slight injuries reduction. Total travel distance per day by all motorcyclists in the household shared equal probabilities in influencing motoryclist’s WTP for both 15% and 25% slight injuries reductions. Groups of motorcyclists aged between 55 and 64 years old prefered 25% to 15% slight injuries reduction compared with younger motorcyclists.
Keywords: Willingness to Pay, Motorcyclists, Slight Injuries Reduction, Logistic Regression